Calibration of Airblast Sprayers - Masoud Salyani (EDIS)
This document is Circular 1435, one of a series of the Agricultural and  Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Date reprinted with permission: April 2003.